PENERAPAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI PENGUKURAN KELAS III SDN MULYASARI 1 - Ajeng Mayangsari; Al-Amin (ADIBA : JOURNAL OF EDUCATION, 2026)
Mathematics learning in elementary schools is still a challenge for some students, especially in understanding material related to the concept of measurement. This problem was also found in third-grade students of SDN Mulyasari 1 who still had difficulty in understanding units of measurement and their application in daily activities. This condition is influenced by the learning process which still tends to be teacher-centered so that students are less actively involved in understanding the material. This study aims to determine how the application of the Contextual Teaching and Learning (CTL) method can help improve students' understanding of measurement material. The study used a Classroom Action Research (CAR) approach which was implemented in two cycles. Each cycle includes the planning stage, action implementation, observation, and reflection. Data collection was carried out through observation, learning outcome tests, and documentation. The application of the CTL method was carried out by linking measurement material with experiences close to students' lives. In the learning process, students were invited to practice directly using simple measuring tools and observing objects around the school environment. This method helps students understand the concept of measurement more realistically and not only based on theoretical explanations. The results of the study showed that the application of the CTL method was able to improve students' understanding of measurement material. This is evident in the improvement in student learning outcomes in each research cycle. Therefore, the CTL method can be an effective alternative for mathematics learning to help students understand measurement concepts more easily, especially at the elementary school level.